ANALISIS FAKTOR PENYEBAB BERALIHNYA MASYARAKAT DALAM PENGGUNAAN SUMUR GALIAN MENJADI SUMUR BOR DI KECAMATAN BARUMUN KABUPATEN PADANG LAWAS - Hasibuan, Hadomuan; Harefa, Meilinda Suriani (Jurnal Samudra Geografi, 2025)
This research investigates the reasons why people in Barumun District, Padang Lawas Regency, are switching from hand-dug wells to boreholes. Conducted in November 2023, the study used a qualitative approach, employing observations, questionnaires, and interviews with residents who have already made the switch. The findings reveal several key drivers for this change. Firstly, there is a desire for easier, faster, and more energy-efficient access to groundwater. Secondly, safety concerns, such as livestock falling into the hand-dug wells, play a significant role. Thirdly, the decline in groundwater levels has caused many hand-dug wells to dry up and become unreachable. The community perceives that replacing dry hand-dug wells with boreholes is an effective solution. Consequently, the role of hand-dug wells in the community has significantly diminished, with many no longer being used.